FORMULASI DAN UJI AKTIVITAS ANTIBAKTERI SEDIAAN HIDROGEL EKSTRAK ETANOL DAUN KELOR - Werawati, Ayu; Dewi, Bheta Sari; Hasanah, Uswatun; Aulia, Gina; Zahra, Annisa Fairuz (STIKes Kharisma Persada, 2024)
Acne vulgaris is an inflammatory skin disease that is widespread in 85% of the human population. This disease occurs when hair follicles are blocked by dead skin cells. In some cases, bacteria such as Staphylococcus sp. triggers the inflammation in acne Moringa leaves are known to have potential antibacterial activity against acne-causing bacteria, such as Staphylococcus aureus. The aim of this research is to develop and evaluate a hydrogel preparation containing ethanol extract of Moringa oleifera L. leaves as an alternative treatment for acne. This research was carried out using an experimental method involving hydrogel formulation with varying concentrations of Moringa leaf extract of 4%, 7% and 10%. The evaluation carried out included organoleptic tests, homogeneity, pH, spreadability, adhesive power, physical stability, and antibacterial activity against Staphylococcus aureus. The research results showed that all hydrogel formulations met the specified quality standards, with appropriate pH, good spreadability and adhesion, and adequate physical stability. The antibacterial activity of the hydrogel also showed relatively strong effectiveness at extract concentrations of 4%, 7% and 10%. This research indicates that Moringa leaf extract hydrogel has the potential to be an effective topical preparation for the treatment of acne. Further research can be carried out by exploring the potential anti-inflammatory activity of the ethanol extract of Moringa oleifera leaves